Pelatihan Microsoft Word Dan Pengembangan Digital Marketing Melalui Blogger Desa Menturus - Agustina, Ulfa Wulan; Ismail, Ismail; Shobaroh, Nuris Lailatus; Alawi, Moh; Siswoyo, Tri; Imelda, Laila (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to evaluate the effectiveness of Microsoft Word training and digital marketing development through the Blogger platform in Menturus Village. The methods used are interview and observation methods involving 15 participants, consisting of local business actors and students of SDN Menturus. The approach was carried out using the interview and observation methods. The results of the study showed a significant increase in skills in using Microsoft Word and digital marketing capabilities. These findings indicate that technology-based training can empower rural communities in facing marketing challenges in the digital era, as well as encourage local economic growth.